2016
DOI: 10.13005/ojc/320602
|View full text |Cite
|
Sign up to set email alerts
|

The Electrochemical Behavior of Titanium Improved by Nanotubular Oxide Formed by Anodization for Biomaterial Applications: A Review

Abstract: Titanium oxide nanotube is gaining prominence in many applications like solar energy, sensors, catalyst and biomaterials. In this paper, we briefly review the electrochemical behavior of titanium oxide nanotube prepared by anodization in simulated body fluids. The electrochemical behavior of TiO 2 nanotube depends on its morphology and surface properties. When titanium oxide nanotube formed by anodization, these surface properties are depending strongly on two factors, the parameters of anodization process and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 87 publications
1
6
0
Order By: Relevance
“…However, Al-Swayih have synthesized TiO 2 nanotubes at 30 and 40 V and have observed that the increase in the nanotube length causes a defect surface, which is attributed to the enhanced rate of chemical dissolution at high potential. [17] The same explanations were reported in previous works; [18,25,26] the authors argue that for high applied anodizing voltage, the chemical dissolution of TiO 2 layer weakens the Ti─O bond and produces a porous and random morphology, unlike to a self-organized structure. The chemical composition obtained by EDS characterization (Figure 1b) indicates oxygen deficiency (44.86% O, 33.51% Ti).…”
Section: Morphological Characterizationsupporting
confidence: 67%
See 3 more Smart Citations
“…However, Al-Swayih have synthesized TiO 2 nanotubes at 30 and 40 V and have observed that the increase in the nanotube length causes a defect surface, which is attributed to the enhanced rate of chemical dissolution at high potential. [17] The same explanations were reported in previous works; [18,25,26] the authors argue that for high applied anodizing voltage, the chemical dissolution of TiO 2 layer weakens the Ti─O bond and produces a porous and random morphology, unlike to a self-organized structure. The chemical composition obtained by EDS characterization (Figure 1b) indicates oxygen deficiency (44.86% O, 33.51% Ti).…”
Section: Morphological Characterizationsupporting
confidence: 67%
“…The physiological environment of the human body was simulated with Hank's solution for in vitro corrosion studies; its chemical composition is given in Table 1. [6,17,22] The electrochemical impedance spectroscopy (EIS) studies were conducted in AC-frequency domain using Biologic SP-150 system from 100 kHz to 10 mHz, with 5 mV amplitude around the open circuit potential (OCP). The temperature was thermostatically kept at 37°C, and the pH was measured to be 7.40.…”
Section: Electrochemical Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of the nature of the electrolyte on the growth of an oxide film on titanium in alkaline and acidic solutions is shown in [17]; however, the effect of the electrolysis regime is not studied. The electrochemical fabrication and behavior of TiO 2 nanotubes is considered in [18]. The properties of nanotubes depend on the anodizing conditions; however, continuous films must be used to coat the implants.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%